Aktivitas Antioksidan Ekstrak Kulit Wuru (Antioxidant activity of Wuru Bark Extractives) - Arief H Prianto; Annisa Alfira; Eka Putri (Jurnal Ilmu dan Teknologi Kayu Tropis, 2016)
Wuru (Cinnamomum cinereum Gamble) has many compounds which are potential as medicine. It’s spread out in Java, Sumatera and Kalimantan. Research of antioxidant activity of wuru barks is still limited. The objective of this study was to evaluate the antioxidant activity of wuru bark extract and its chemical composition. The barks were extracted using n-hexane, ethyl acetate and methanol. Antioxidant capacity was determined by 1,1-diphenyl-2-pikril-hidrazil (DPPH). Vitamin C was used as a comparison. Three fraction of methanol extract showed very high antioxidant activity. They have IC50 value 6.2, 7.89, and 13.3 ppm, respectively.